Intellectual property and innovation protection : new practices and new policy issues - Lallement, Rémi (Innovation, entrepreneurship and management series. Innovation between risk and reward set, 2017)
This book analyses the various ways in which intellectual property (IP) operates in relation to innovation activity. It reflects on the "classical" issues of the IP system related to the necessity of protecting risky and often costly investments undertaken by firms and others players involved in the innovation process. Beyond this, it stresses the numerous challenges addressed by contemporary technological and societal change, especially in a world where the digital revolution is rapidly transforming the way in which innovation is organized. In this context, the new corporate IP and innovation practices call for responses on the part of public policies.